(untitled) (CIPEEX, 2025)
Diabetes mellitus is a chronic endocrine-metabolic disease that is treated with medications that improve insulin production or action, as well as the administration of exogenous insulin. Therefore, insulin must be stored and handled correctly in order to minimize application errors and ensure glycemic control. Focusing on this idea, the overall objective of this project is to assess the knowledge of Pharmacy students at the Evangelical University of Goiás regarding the handling and administration of insulin. The assessment was carried out using a questionnaire to evaluate errors and correct answers regarding the main guidelines for patients on the handling and administration of insulin. The results showed that the sub-items related to insulin homogenization, correct selection of application sites, time of removal from the refrigerator, and needle protection had the highest error rates. On the other hand, the items with the highest accuracy refer to the appropriate choice of application site, correct handling in case of frozen insulin, and the crucial importance of asepsis. The study revealed gaps in the students’ knowledge of insulin therapy, indicating the need to reinforce pharmaceutical training and promote new researches to address these deficiencies and, consequently, increase the safety and effectiveness of diabetes mellitus treatment.